Effect of impeller types on saponification reaction using stirred tank reactor (Talenta Publisher, 2019)
The choice of impeller type is an important factor in maximizing the performance of a stirred tank reactor in saponification process. This study aims to determine the type of impeller that can produce the highest reaction rate by taking into account changes in alkali concentration in saponification reactions so as to obtain a shorter residence time. The saponification process was carried out by reacting 30% oil with alkali (KOH) at operating conditions 70C, stirring speed of 400 rpm for 45 minutes using 4 types of impellers namely paddle-2 blades, pitch blade turbine 45°-2 blades, paddle-4 blades, pitch blade turbine 45°-4 blades. Testing of alkali concentration was carried out every 5 minutes until the reaction was complete. Alkali concentration was obtained at the end of the reaction using a paddle-2 blades impeller of 0.182 M with a conversion of 97.35%, a pitch blade turbine 45°-2 blades of 0.142 M with a conversion of 97.93%, paddle-2 blades of 0.106 M with conversion of 98.46%, pitch blade turbine 45°-4 blades of 0.100 M with conversion of 98.54%.